Combined coronary artery bypass graft and liver/kidney transplantation in a liver failure patient with acute on chronic kidney failure and antiphospholipid syndrome. Issue 10 (5th May 2022) - Lin, Emily; Bratton, Charles; Nguyen, Minh‐Tri; Chung, Joshua; De Vera, Michael; Rakoski, Mina
Abstract : Coexisting coronary artery disease (CAD), end‐stage liver disease (ESLD), renal failure, and hypercoagulable state poses a formidable clinical challenge. Here, we discuss the first known case of a patient with antiphospholipid syndrome (APLS), ESLD complicated by hepatorenal syndrome (HRS), and severe CAD who successfully underwent combined coronary artery bypass grafting (CABG) and simultaneous liver/kidney (SLK) transplant. Abstract : A patient with decompensated liver disease with hepatorenal syndrome, coronary artery disease, and antiphospholipid syndrome successfully undergoes combined coronary artery bypass grafting and simultaneous liver/kidney transplant.